Coordination and critical mass in a network market: An experimental investigation - Bradley J. Ruffle; Avi Weiss; Amir Etziony (Bar-Ilan University, Department of Economics, 2010)
A network market is a market in which the benefit each consumer derives from a good is an increasing function of the number of consumers who own the same or similar goods. A major obstacle that plagues the introduction of a network good is the ability to reach critical mass, namely, the minimum number of buyers required to render purchase worthwhile. This can be likened to a coordination game with multiple Pareto-ranked equilibria. We introduce an experimental paradigm to study consumers' ability to coordinate on purchasing the network good. Our results highlight the central importance of the level of the critical mass.
Keywords: C92; L19; 330; experimental economics; network goods; coordination game; critical mass; Experimentelle Ökonomik